Frequency of tuberculosis among diabetic patients in the People's Republic of China - Wang HT; Zhang J; Ji LC; You SH; Bai Y; Dai W; Wang ZY (Dove Medical Press, 2014)
Hong-Tian Wang,1 Jing Zhang,1 Ling-Chao Ji,1 Shao-Hua You,1 Yin Bai,1 Wei Dai,2 Zhong-Yuan Wang31Department of Otorhinolaryngology, Head, and Neck Surgery, Chinese PLA General Hospital, 2Department of Medical Record Administration, Chinese PLA General Hospital, 3The 3rd TB Department, Chinese PLA 309 Hospital, Beijing, People's Republic of ChinaAbstract: The People's Republic of China has nearly the highest incidence of both diabetes mellitus (DM) and tuberculosis (TB) worldwide. DM increases the risk of TB by two to three times and adversely affects TB treatment outcomes. The increasing epidemic of DM in the People's Republic of China is due to decreased physical activity, unhealthy diet, and obesity. Over the last 20 years, the excellent free China National Tuberculosis Program has been set up, and the “DOTS” (directly observed treatment + short-course chemotherapy) model for TB control has successfully reduced the burden of TB, but the disease is still a considerable problem. Given the high burden of TB and DM in the People's Republic of China and the relationship between the two diseases, it is sensible to screen DM patients for TB. A bidirectional screening of the two diseases was conducted in the People's Republic of China from 2011 to 2012, which identified a TB incidence in patients with DM of about 958 per 100,000. Here, we report the findings of our recent study on the incidence of TB among diabetic patients in the People's Republic of China. The data agree with those of previous reports.Keywords: TB, diabetes mellitus, complications, screening